An exploration of the experiences of women treated with radiotherapy for breast cancer: Learning from recent and historical cohorts to identify enduring needs. (April 2019) - Llewellyn, Alison; Howard, Claire; McCabe, Candida
Abstract: Purpose: Recent decades have seen improvements in UK breast cancer services and treatments. Despite this, it is recognised that a range of patients' psychological and emotional needs remain unmet, both at the time of treatment and into survivorship. Using data from two distinct cohorts of women: those treated with radiotherapy for breast cancer historically, and women treated more recently, this study sought to identify and explore those needs and concerns that have continued to persist, despite advances in treatment and care. Method: Data from N = 13 semi-structured interviews were analysed using Interpretative Phenomenological Analysis. An heuristic framework was applied to extract themes common to both participant cohorts. Results: Participants' data evidenced an enduring vulnerability amongst cancer patients that has not diminished with new treatment pathways. Themes common to both cohorts highlighted the ongoing importance of personal factors such as resilience, and strategies to help retain a sense of normality. Extrinsic support was important too, especially high quality communication by healthcare professionals and having access to ongoing emotional support from others, particularly when active treatment ends. Participants' suggestions for future service development included the provision of ongoing continuity of care and greater access to emotional support services. Conclusions: This study highlights the psychological needs and concerns of breast cancer patients that have persisted, despite the many advances in patient-centred care. Findings are of value to nurses and other healthcare professionals in highlighting the ongoing importance of recognising, acknowledging and addressing patients' concerns and needs, even within current cancer care pathways. Highlights: ∙ This study comprised two distinct cohorts: women treated for breast cancer historically, and women treated more recently. ∙ The study aimed to identify and explore needs and concerns that have continued to persist despite advances in care. ∙ Themes demonstrated the importance of intrinsic resources and emotional support within and beyond the acute care pathway. ∙ Findings highlight the ongoing importance of addressing patients' concerns and needs.